The processing and interpretation of sich in German as a second language by Japanese and Korean learners - Sperlich Darcy (Zeitschrift für Sprachwissenschaft)
This study investigates the processing and interpretation of the reflexive pronoun sich by Japanese and Korean learners of German as a second language. This is explored through the emergentist reflexivity approach, which hypothesizes that these learners will utilize their first language pragmatic strategies to bind sich, instead of syntactic binding found in German. Employing psycholinguistic methodology, a self-paced reading experiment is undertaken, utilizing antecedent judgements and introspective measures. The results show that instead of using the pertinent German syntax to bind sich, the learners continue to fall under the influence of their first language pragmatics. These results are discussed against the larger picture of reflexive theory, showing how German as a second language can advance our understanding of reflexivity.